Eksperimentasi Pembelajaran Matematika Dengan Strategi Problem Posing Berbasis Assessment For Learning Terhadap Hasil Belajar Ditinjau Dari Tingkat Keaktifan Siswa Kelas VII Semester Genap SMP Muhammadiyah 7 Surakarta Tahun 2014/2015 - Sulistioningsih, Rika; , Drs. Slamet HW, M.Pd (2015)
This study aims to: (1) know the effect of the implementation of problem posing strategy based assessment for learning on learning outcomes of students in learning mathematics. (2) know the effect of the level of activity students on learning mathematics outcomes of students. (3) know the interaction between problem posing strategy based assessment for learning and the level of activity on learning outcomes of students' learning of mathematics. The research is a quasiexperiment. The population of this study were all of seven grade students at SMP Muhammadiyah 7 Surakarta in 2014/2015 academic year. Samples used in this study were 60 students. Samples taken by random sampling technique.The selected sample is VII C as the experimental class and VII E as the class control. Mathematics learning outcome data were collected with the test method. Data collected were tested hypotheses using two way ANOVA with α = 5% shows that: (1) FA = 5,01487 > Ftabel = 4,02 which means that there is influence between the problem posing based assessment for learning strategy and the ekspositori strategy to results mathematics learning. Based on the average of the student's result, using problem posing based assessment for learning is better than the ekspositori strategy (